Reinterpretasi Hadis Penaklukan Konstantinopel Perspektif Fazlur Rahman - Harel Bayu Paizin (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2020)
This paper discusses the criticism conveyed by Rahman on the understanding of hadith that has been developed in the midst of Islamic societies regarding the hadith about the conquest of Constantinople, where so far the hadith about the conquest of Constantinople is believed to be the main driver of Islamic commanders to conquer Constantinople. But Fazlur Rahman denied it by stating that the hadith was a hadith that emerge during the period of defamation which was used by certain groups to support their ambitions. To support his suspicion, Rahman offers a methodology called the theory of historicity, where each hadith must be seen first in terms of the history that follows it. The results obtained from the hadith about the conquest caused a shift in understanding that had been believed by Muslims that the conquest of Constantinople was inspired by the hadith that was revealed by the Prophet Muhammad.